Influence of cyclodextrins on the photostability of selected drug molecules in solution and the solid-state - B. D. Glass; M. E. Brown; S. Daya; M. S. Worthington; P. Drummond; E. Antunes; M. Lebete; S. Anoopkumar-Dukie; D. Maharaj (International Journal of Photoenergy)
The photostability of selected drug molecules, including furosemide, prochlorperazine, diclofenac, piroxicam, midazolam and nifedipine was studied, the kinetics of photodegradation, identification of the photodegradants investigated and mechanisms of photodegradation proposed. Selected cyclodextrins altered the photodegradation profiles of diclofenac, piroxicam, midazolam and nifedipine by either accelerating or retarding the rate of photodegradation and generating novel photodegradants.